Comparison of extraction techniques for three Calophyllum species and their antioxidant activity - Ramli, Siti Norhafizah; Aminudin, Nurul Iman; Ahmad, Farediah; Darnis, Deny Susanti (2018)
Calophyllum is a pan-tropical genus belongs to the Guttiferae family and locally known in Malaysia as ‘bintangor’. There has been a continual interest to further investigate the phytochemistry of Calophyllum sp since this genus is a rich source of active secondary metabolites which showed anti-HIV, cytotoxicity and antimicrobial properties. This study was conducted to investigate the effect of extraction techniques on the phytochemicals content and antioxidant activity of the barks, leaves and heartwood extracts of three Calophyllum species, C. incrassatum, C. rubiginosum and C. canum. Soxhlet and maceration extraction techniques by using methanol as solvent were chosen in this study. Maceration extraction technique produced higher percentage yield compared to Soxhlet extraction for leaves and barks of the three Calophyllum species. Highest percentage yield was obtained from bark extract of C. canum (21.76%) followed by bark extract of C. rubiginosum (20.24%) and leaves extract of C. rubiginosum (19.34%). Meanwhile, Soxhlet extraction technique gave higher percentage yield compared to maceration technique for heartwood extracts of all samples. The phytochemical screening test revealed all the extracts contain tannin, phenol, flavonoid, terpenes, cardiac glycoside, coumarin and phytosterol. The antioxidant activity of all extracts was tested by determining the Total Phenolic Content and DPPH radical scavenging activity. The highest Total Phenolic Content was obtained from Soxhlet extraction technique. The bark extract of C. canum displayed the highest phenolic content (461.90 mg GAE/g) followed by bark extract of C. incrassatum (394.52 mg GAE/g) and leave extract of C. incrassatum (227.89 mg GAE/g). Meanwhile, the extracts from Soxhlet extraction technique gave higher antioxidant activity compared to maceration extraction. The bark extract of C. canum showed the lowest IC50 value (3.07 µg/mL) followed by bark extract of C. incrassatum (5.12 µg/mL) and leave extract of C. incrassatum (5.93 µg/mL). Pearson’s correlation test showed positive correlation between Total Phenolic Content and DPPH radical scavenging activity.